Aberrant Right Subclavian Artery: Correlation Between Fetal and Neonatal Abnormalities and Abnormal Genetic Screening or Testing. (10th January 2017) - Ranzini, Angela C.; Hyman, Francine; Jamaer, Emily; van Mieghem, Tim
Abstract : Objectives: To determine whether fetuses with an isolated aberrant course of the right subclavian artery (ARSA) have increased risk for chromosomal abnormalities, including trisomy 21 or 22q11 deletion. Methods: We performed a retrospective chart review of all fetuses with antenatally diagnosed ARSA. Data were collected from fetal anatomic surveys, fetal echocardiograms, noninvasive trisomy 21 screening programs, invasive genetic studies, and neonatal records. Results: Seventy‐nine fetuses with ARSA were identified at 20.3 ± 3.8 weeks' gestation. Forty‐eight fetuses underwent chromosomal evaluation. Of those, seven had trisomy 21. Four other fetuses had unusual karyotype abnormalities. All fetuses with genetic anomalies had additional aberrant ultrasound findings. There were three spontaneous fetal deaths (trisomy 21‐2 and Wolf‐Hirshhorn‐1). Nine pregnancies were terminated because of abnormalities and one died as a result of hypoplastic left heart syndrome. No neonate was found or suspected to have 22q11.2 deletion. The ARSA was isolated in 43 fetuses; all had unremarkable neonatal outcomes, and none were readmitted within 6 months after discharge. Conclusions: As an apparently isolated finding, ARSA is benign and not associated with trisomy 21 or 22q11.2 deletion. The finding of ARSA, however, warrants a detailed fetal ultrasound. All fetuses with ARSA and genetic anomalies had additional ultrasound findings.